Kinematic detection of a planet carving a gap in a protoplanetary disk - Pinte, C; van der Plas G; Ménard, F; Price, D J; Christiaens, V; Hill, T; Mentiplay, D; Ginski, C; Choquet, E; Boehler, Y; Duchêne, G; Perez, S; et al. (Nature astronomy, 2019)
We still do not understand how planets form or why extrasolar planetary systems are so different from our own Solar System. However, the past few years have dramatically changed our view of the disks of gas and dust around young stars. Observations with the Atacama Large Millimeter/submillimeter Array and extreme adaptive-optics systems have revealed that most—if not all—disks contain substructure, including rings and gaps1–3, spirals4–6, azimuthal dust concentrations7 and shadows cast by misaligned inner disks5,8. These features have been interpreted as signatures of newborn protoplanets, but the exact origin is unknown. Here we report the kinematic detection of a few-Jupiter-mass planet located in a gas and dust gap at 130 au in the disk surrounding the young star HD 97048. An embedded planet can explain both the disturbed Keplerian flow of the gas, detected in CO lines, and the gap detected in the dust disk at the same radius. While gaps appear to be a common feature in protoplanetary disks2,3, we present a direct correspondence between a planet and a dust gap, indicating that at least some gaps are the result of planet–disk interactions.Pinte et al. report the kinematic detection of a few-Jupiter-mass planet orbiting at 130 au from the young star HD 97048. The radial position of the planet coincides with a gap in both the gas and dust components of the protoplanetary disk, showing that at least some gaps can be linked to the presence of planets.